Diclofenac Sodium Adsorption onto Montmorillonite: Adsorption Equilibrium Studies and Drug Release Kinetics - Manpreet Kaur; Monika Datta (Adsorption Science & Technology)
The aim of the present work was to investigate the role of montmorillonite clay as an oral drug delivery carrier for in vitro controlled release of anti-inflammatory drug diclofenac sodium (DS). For this purpose, the adsorption behaviour of DS onto the clay was studied as a function of pH of the aqueous drug solution, contact time, initial drug concentration and clay dosage. The clay–drug composites synthesized were subsequently characterized by X-ray diffraction studies, Fourier transform-infrared studies, differential scanning calorimetric analysis, thermogravimetric analysis, zeta-potential measurement, scanning electron microscopic and high-resolution transmission electron microscopic techniques. A drug loading of 497 mg/g was obtained in case of intercalated clay–drug composite. The in vitro drug release studies of the synthesized clay–drug composites in simulated gastric fluid (pH 1.2) showed no release, whereas a prolonged drug release profile was obtained for the intercalated clay–drug composite in simulated intestinal fluid (phosphate-buffer saline 7.4) in comparison with the pristine drug.